Answer:
Step-by-step explanation:
At first, lets find the distance from one point to the other.
[tex]d(A,B)=\sqrt{(x_{A}-x_{B} )^2 +(y_{A}-y_{B} )^2 } \\d(A,B)=\sqrt{(2-0 )^2 +(-2-4 )^2 } \\d(A,B)=\sqrt{4 +36 } = \sqrt{40 } = \sqrt{4 * 10 } = 2\sqrt{10}[/tex]
The same way, you can find that:
[tex]d(A,C)= 2\sqrt{10}\\d(A,B)= 2\sqrt{20}[/tex]
Since the triangle has only its two sides equal to each other (AB = AC),
it's an isosceles one.
As long as the angles are concerned, we gotta "cheat". In other words, we see that:
[tex]AB^2 + AC^2 = (\sqrt{40})^2 + (\sqrt{40})^2 = 40 + 40 = 80\\ AB^2 + AC^2 = 80 = (2\sqrt{20})^2 = BC^2\\AB^2 + AC^2 = BC^2[/tex]
By the inverse of pythagorean theorem, we know that if the above equation holds, then we have a right-angled triangle. That is to say that,
A = 90
Since its an isosceles triangle, AB = AC,
B = C = (180 - A)/2 = 45 degrees